The main areas of application of IoT technologies in agriculture - Leonova Y.V.; Skvortsov E.A.; Gusev А.S.; Skvortsova E.G. (E3S Web of Conferences, 2023)
The relevance of the research topic is determined by the significant pace of implementation of IoT technologies in agriculture and the poor theoretical development of their application. The purpose of the study is to identify the main areas of application of IoT technologies in agriculture. The scientific novelty is the theoretical provisions on the directions of the use of IoT technologies in the industry. The analysis of scientific publications in this area of research has been carried out and the main areas of application of IoT technologies in the industry have been clarified, and their characteristics have been given. The main applications of IoT technologies in agriculture include smart (smart farm, smart field) and intelligent (real-time data collection) environments, predictive analysis of crop yields and animal productivity, various measurements, predictive maintenance, resource consumption control and remote management of machines and equipment. The results of the study allow deepening knowledge about IoT technologies used in agriculture, contributing to their systematization, expanding the range of IoT types used by agricultural organizations.